The DRESS trial: a feasibility randomized controlled trial of a neuropsychological approach to dressing therapy for stroke inpatients - Walker, Marion F.; Sunderland, Alan; Fletcher-Smith, Joanne; Drummond, Avril E.R.; Logan, Pip; Edmans, Judi A.; Garvey, Katherine; Dineen, Robert A.; Ince, Paul; Horne, Jane; Fisher, Rebecca J.; Taylor, Jenny L. (SAGE, 2012)
Objective: To investigate two approaches to treating patients with persistent dressing problems and cognitive difficulties following stroke.